CP-138 Evaluation of pharmacoeconomic interventions in neurological patients treated with immunoglobulins. (24th February 2014) - Sommer, C; Brunnert, M; Fricke, S; Wallenstein, L; Baehr, M; Langebrake, C
Abstract : Background: Intravenous immunoglobulins (IVIG) are used in various neurological diseases, sometimes off-label and with varying reliability of evidence. High treatment cost, the worldwide shortage of IVIG and the special requirements of the German reimbursement system are a challenge for clinical pharmacists in controlling the rational use of IVIG. Purpose: To capture the economic benefit of clinical pharmacists' interventions regarding IVIG treatment, considering the German reimbursement system. Materials and methods: Retrospective analysis of 120 patients treated with IVIG in 464 cycles from January 2011 to August 2013 at the University Medical Centre Hamburg-Eppendorf. Data were taken from a Computerised Physician Order Entry (ATCHost) and an electronic patient record system (Soarian). Any savings due to the intervention of drug and dose selection were included. Avoided costs of saved bed days were calculated with the official data from the Federal and the State Statistics Offices. Results: Clinical pharmacists' interventions saved costs of 368, 128 € during the observation period. Savings were achieved by daily interventions in the selection of IVIG, their dose and duration of treatment according to current guidelines, checking and correcting the documentation of IVIG administration to ensure correct procedures and just in time delivery. In addition 234 bed days were saved. This corresponds to an amount of 101, 261 € or 120, 510 € including bed day savings. Overall the amount is approximately 469, 390 to 488, 638 €. That translates to statistical cost savings of 4, 080 € per patient during the observation period. Conclusions: Clinical pharmacists should be well-integrated into clinical practice of neurological wards because they avoid costs and reduce length of stay. To our knowledge this is the first report of clinical pharmacists' impact on cost saving in IVIG treatment. No conflict of interest.